Distances wired Relation for different connected of Server-Computer to Client Computers Packet sizes relation for different Distances wired connected of Server-Computer to Client Computers - Kamaran HamaAli.A.Faraj; Nashih Mohamad Najeb; Bahar Saderuldeen Nooor uldeen; Sara Adnan Anwar (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Performance Analysis of static website over computer networks with utilized of Unshielded Twisted Pair (UTP) in distances variety which located to the first layer of TCP/IP and called physical layer. investigates of paper is physical layer components (only cable distance) for network Quality of Service (QoS) in private Network (PRN) and Public network (PUT), idea for this paper stems from the fact that computer networks have become more and more popular over the last decade. Internet over networks has a great role to speed up all business and make life much easier, faster; more organize and cheaper Test the performance of the LANs PRN and Dialup PUN. Determinate best response time in PRN will be found out with different cable distance; furthermore the public network PUN will be tested by the distance of cities. Background information on computer networks in general and on Private and Public Networks in particular is provided. The LAN design provided is by no means the only possible way of implementing a Local Area Network. Nevertheless the far-off from the Head-quarter is connected by public network landline telephone. The private and public networks utilized in reason of solving traffic/bottle neck problem. Performance by response time is an important factor and hot topic in the world of computer communication and networking. The constant size of static website installed on Server-side, also connected in different length of cable UTP to clients in order to test and discover lowest response time.